2015
DOI: 10.17261/pressacademia.2015211510
|View full text |Cite
|
Sign up to set email alerts
|

R D expenditures and earnings targets: evidence from France

Abstract: Research and development (R&D) investments reduce current-period earnings while the benefits associated with the investments occur in the future. This problem implies an earnings management tool to boost short-term performance. While there is much evidence regarding managerial discretion through R&D capitalization, empirical studies that directly examine managerial discretion through R&D expenditure adjusting have not been widely provided in the European context. This paper seeks to determine if earnings targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 84 publications
1
14
0
Order By: Relevance
“…Study results also supported by Docherty & Hurst (2018), movements of stock mar-ket momentum could lead to myopia in investments as firm value is affected by investor's perception of trust about stock's future value than its fundamental value, thus affecting market-to-book equity ratio of a firm. It should be noted that several manufacturing companies during the study experienced capital deficiency conditions in their financial statements and set aside priorities on R&D expenditures, even though Guidara & Boujelbene (2015) found that French companies that averaged 46% of the company's total sales for R&D investments were able to enjoy investment opportunities are almost double their market-to-book equity ratio, if R&D funding can be a priority within the company then the potential for this increase can also occur in the manufacturing industry in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Study results also supported by Docherty & Hurst (2018), movements of stock mar-ket momentum could lead to myopia in investments as firm value is affected by investor's perception of trust about stock's future value than its fundamental value, thus affecting market-to-book equity ratio of a firm. It should be noted that several manufacturing companies during the study experienced capital deficiency conditions in their financial statements and set aside priorities on R&D expenditures, even though Guidara & Boujelbene (2015) found that French companies that averaged 46% of the company's total sales for R&D investments were able to enjoy investment opportunities are almost double their market-to-book equity ratio, if R&D funding can be a priority within the company then the potential for this increase can also occur in the manufacturing industry in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Variable measurement of market-to-book equity is based on Lundstrum (2002) who designed this approach as Q-theory of investment implies that investment opportunities are sufficient to explain all investment activity, also the usage of market-to-book equity ratio to control the variation in firm-year investment and making it a good proxy for investment opportunities. This variable is also used by Guidara & Boujelbene (2015) who stated greater investment opportunity (measured with market-tobook equity ratio) could make it costly to cut R&D expenditure, so controlling this variable could represent discretionary R&D expense treatment, as myopia in investment is calculated through R&D expense.…”
Section: Method Data and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A further paper on this topic was published by R. Guidara and Y. Boujelbene (2015), who on the basis of 800 firm-year observations (80 French companies qualified as R&D intensive in the reports within [2005][2006][2007][2008][2009][2010][2011][2012][2013][2014] showed that firms manage R&D expenditures to avoid earnings losses and decreases. The empirical part of the study provides evidence that decisions concerning R&D budgets are used to help achieve earnings targets.…”
Section: The Literature and The Hypothesismentioning
confidence: 99%
“…There are also papers that focus on a particular type of accruals. For instance, Rasmussen (2013) analyzes earnings management on the basis of revenue recognition, while Guidara and Boujelbene (2015), Shust (2015) and Garanina, Nikulin and Frangulantc (2016) consider accounting treatment of R&D costs as an earnings management tool. Much attention in recent years has also been given to real earnings management that is treated as an alternative to accrual-based earnings management (e.g., Zang, 2012;Chan et al, 2015;Malik, 2015).…”
mentioning
confidence: 99%